Comparison of materno‐fetal predictors and short‐term outcomes between early and late onset pre‐eclampsia in the low‐income setting of Douala, Cameroon. Issue 2 (30th May 2018) - Nguefack, Charlotte T.; Ako, Mangwi A.; Dzudie, Anastase T.; Nana, Théophile N.; Tolefack, Paul N.; Mboudou, Emile
Abstract: Objective: To describe and compare materno‐fetal predictors and short‐term outcomes of early onset pre‐eclampsia (EOPE) and late onset pre‐eclampsia (LOPE) in Douala, Cameroon. Methods: The present prospective hospital‐based cross‐sectional study included women with pre‐eclampsia attending obstetric units at four hospitals in Douala between December 1, 2016, and April 30, 2017. To determine maternal predictors, sociodemographic and medical data were recorded using a pretested questionnaire. Pregnancy outcomes, and maternal and fetal adverse events were recorded. Univariate and multivariate logistic regression analyses were used to examine associations. Results: Of 170 participants, 58 (34.1%) had EOPE and 112 (65.9%) had LOPE. EOPE was associated with higher incidences of chronic hypertension ( P= 0.027) and history of pre‐eclampsia ( P= 0.003) compared with LOPE. Higher incidences of nulliparity and a different partner from prior pregnancy ( P= 0.024) were associated with LOPE. Women with EOPE had higher odds of acute kidney injury (odds ratio [OR] 6.67, 95% confidence interval [CI] 1.73–25.73) and HELLP (hemolysis, elevated liver enzyme, low platelets) syndrome (OR 10.47, 95% CI 1.19–91.9), and lower odds of deliveries without perinatal adverse events (OR 0.19, 95% CI 0.09–0.38), compared with patients with LOPE. Conclusion: In the low‐income setting of Douala, there was a higher rate of LOPE than EOPE. Factors associated with EOPE and LOPE varied, and outcomes were worse for women with EOPE. Abstract : One‐third of women with pre‐eclampsia had early onset pre‐eclampsia (EOPE). The factors associated with EOPE varied. Women with EOPE had adverse maternal and perinatal outcomes.